Understanding of HR Management Policies for Small Businesses Disturbed by the Pandemic Crisis: Small Business Literature Review Study - Widjaja, Gunawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This review discusses the understanding of state policies on human resource management in the field of small and medium-sized businesses that are still plagued by the pandemic. For this purpose, we have conducted a series of data searches on online databases, especially scientific journal publications that publish HR issues and strengthen small businesses. Our data is obtained from secondary data from well-known publications such as Research gate, Taylor&Francis, Google Book, Sagepub, and databases published by the Indonesian Government related to policies and regulations for small and medium enterprises. At the same time, Indonesia is still plagued by pandemics. Then our data with a phenomenological approach to explore all available data so that we can find answers to this study with available and valid principles. Among other things, our studies involved evaluation, system coding, and high interpretation before we got a summary. The results include that Micro, Small, and Medium Enterprises contribute to the National Gross Domestic Product and have an essential role in economic recovery. The Government is committed to supporting MSMEs to survive, develop, and grow amid the challenges of the pandemic.